LEGAL PROTECTION OF ANGGUK DANCE AS A TRADITIONAL CULTURE - Purnomo, Vicki Dwi (JIPRO: Journal of Intellectual Property, 2022)
This study analyzes the legal protection of the Angguk dance for commercial purposes and provides an overview of intellectual property rights and traditional cultural expressions. Furthermore, the author also mentions the legal protection of the Angguk dance as a traditional culture and legal protection at the national level. Next, we analyze the concept of profit sharing. This study provides practical and academic guidance in a scientific field, namely legal research, for those who are interested in advancing the legal protection of the Angguk dance as a traditional culture from the perspective of commercial interests and the subject of analysis. You are expected to provide feedback in a timely manner. of profit sharing. The research method used in this study is a normative library research method, namely research on legal norms contained in statutory regulations. The author analyzes the legal protection of the Angguk Dance as a traditional culture based on Article 38 of Law Number 28 of 2014.